URGENSI SUMBER DAYA MANUSIA MENUJU APARATUR SIPIL NEGARA POTENSIAL BERBASIS KETANGGUHAN MENTAL-SPIRITUAL - Suhanda Suhanda (Ri'ayah: Jurnal Sosial dan Keagamaan, 2016)
This article explains the importance of human resource potential as a driving force in a organiasi or bureaucracy. The study was conducted with the literature study with reference to a number of previous studies and related literature. From the study represent the importance of human resources in an organization, institution, or bureaucracy. Primarily in a bureaucratic public sector can be used as a reference for building a strong bureaucracy. Civil Administrative State was instrumental as planners, implementers and supervisors holding general duty of government and national development through the implementation of policies and a professional public service, free from political interference, as well as clean of corruption, collusion, and nepotism in the contribution of performance and service support improving the competitiveness of the Indonesian nation. The quality of human resources (HR) is basically determined not only by mastering science and technology, but also the spiritual-mental toughness in creating the human resource potential